(untitled) (International Journal of Engineering and Computer Science, 2017)
In this paper we aim to propose an efficient method to implementing a distributed segment tree. For this purpose we use MapReduce which is a powerful tool in parallel data processing to divide the task among P separate processors. We will exploit parallel processing in order to decrease the time complexity of segment tree implementation and range queries.